The Staging of Jewish Suffering in the Bellum Judaicum: On the Intentions of the Jewish Historian Flavius Josephus - Swoboda, Sören (Vox Scripturae - Revista Teológica Internacional, 2015)
This paper summarizes the purpose, goal, method, structure and principle findings of the monograph “Tod und Sterben im Krieg bei Josephus [Death and Dying in War in the Works of Josephus]” (SWOBODA, Sören. [TSAJ 158]. Tübingen: Mohr Siebeck, 2014), which addresses the intentions of Flavius Josephus and the placement of his historical works within ancient historiography. A special focus is placed on the Bellum, published in 75-79 AD: A broad comparison with non-biographical, more than fragmentarily surviving Greco-Roman historiographies (5th cent. BC to 2nd cent. AD) demonstrates that the work contrasts markedly with non-Jewish historians as well as the Antiquities especially in regard to its ‘tragic’ portrayal of the suffering that overcame the Jews during the Jewish War. As a central intention of the Bellum, Josephus intends to awaken pity among non-Jews with this form of historiographic reporting, which also in the 1st century AD was subject to critique and needed to be justified. He could hope for this pity, because he portrays his people moreover as worthy of admiration and as for the most part innocently suffering.